Biocementation mediated by native microbes from Brahmaputra riverbank for mitigation of soil erodibility - Dhami, Navdeep; Dubey, Anant Aishwarya; K, Ravi; Mukherjee, Abhijit; Sahoo, Lingaraj; Moses, Akindele Abiala (Nature Publishing Group, 2021)
Riverbank erosion is a global problem with significant socio-economic impacts. Microbially induced calcite precipitation (MICP) has recently emerged as a promising technology for improving the mechanical properties of soils. The present study investigates the potential of selectively enriched native calcifying bacterial community and its supplementation into the riverbank soil of the Brahmaputra river for reducing the erodibility of the soil. The ureolytic and calcium carbonate cementation abilities of the enriched cultures were investigated with reference to the standard calcifying culture of Sporosarcina pasteurii (ATCC 11859). 16S rRNA analysis revealed Firmicutes to be the most predominant calcifying class with Sporosarcina pasteurii and Pseudogracilibacillus auburnensis as the prevalent strains. The morphological and mineralogical characterization of carbonate crystals confirmed the calcite precipitation potential of these communities. The erodibility of soil treated with native calcifying communities was examined via needle penetration and lab-scale hydraulic flume test. We found a substantial reduction in soil erosion in the biocemented sample with a calcite content of 7.3% and needle penetration index of 16 N/mm. We report the cementation potential of biostimulated ureolytic cultures for minimum intervention to riparian biodiversity for an environmentally conscious alternative to current erosion mitigation practices.